2018
DOI: 10.3390/f9050281
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Vegetation, Hydrology, and Litter Inputs on Decomposition and Soil CO2 Efflux of Tropical Forests in the Brazilian Pantanal

Abstract: Climate change has the capacity to alter water availability and the litter production of tropical forests, which will alter rates of carbon (C) cycling and storage. We conducted a short-term field experiment in two hydrologically diverse forests in the Brazilian Pantanal to assess the initial response of litter decomposition and soil respiration (Rsoil) to variations in litter pool size. Total annual Rsoil and decomposition significantly declined with litter removal and increased with litter addition, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…According to another study carried out at Acurizal, where three treatments evaluated, namely: control, removal and addition of litter, they observed that its manipulation did not significantly affect the root biomass density in the soil (PINTO et al, 2018).…”
Section: Litter Dynamicsmentioning
confidence: 99%
“…According to another study carried out at Acurizal, where three treatments evaluated, namely: control, removal and addition of litter, they observed that its manipulation did not significantly affect the root biomass density in the soil (PINTO et al, 2018).…”
Section: Litter Dynamicsmentioning
confidence: 99%
“…Although a number of studies have reported that litter inputs significantly affect soil respiration, this can vary with other factors, such as vegetation type (Duan et al, 2018;Han et al, 2015), successional stage (Han et al, 2015), stand age (Xin et al, 2016), experimental study period (Crow et al, 2009;Sayer, 2006;Wang et al, 2009Wang et al, , 2013, climatic conditions (Deng et al, 2007;Liang et al, 2010;Sulzman et al, 2005;Zhang et al, 2016;Zimmermann et al, 2009), the quantity and quality of litter (Bréchet et al, 2018;Deng et al, 2007;Duan et al, 2018), topography (Duan et al, 2018;Zhang et al, 2020), soil temperature and moisture (Fekete et al, 2014;Sulzman et al, 2005), and soil physicochemical properties (e.g., soil pH, soil C:N, soil bulk density) (Pinto et al, 2018;Zhang et al, 2020). In addition, the response of soil respiration to litter inputs can also be influenced by soil microorganisms (e.g., microbial quantity and community structure) (Han et al, 2015;Leitner et al, 2016;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of litter inputs on soil respiration and soil microorganisms is extremely complex. Most studies have found that soil respiration was significantly increased by litter inputs (Bréchet et al, 2018;Kim et al, 2005;Pinto et al, 2018;Sayer et al, 2007;Sulzman et al, 2005;Zhang et al, 2016Zhang et al, , 2020Zimmermann et al, 2009), while only a few have reported that soil respiration was not increased by litter inputs (Fekete et al, 2014;Sun et al, 2005). In contrast, soil microbial biomass has been found to increase (Wu et al, 2017), decrease (Leitner et al, 2016;Wang et al, 2013), or remain unchanged (Leitner et al, 2016) in response to litter inputs.…”
Section: Introductionmentioning
confidence: 99%
“…The SOC differences among three water levels were caused by different soil mineralisation in different environments. Soil mineralisation in aerobic environment (−25 cm) was significantly higher than that in the flooded environment (0, +25 cm) (Qiu et al, 2018), so the SOC at −25 cm water level was lower than the other two water levels. Nevertheless, we considered mainly aboveground litter in this experiment.…”
Section: Contribution Of Leaf Decomposition To the Soil Surface Carbomentioning
confidence: 79%
“…Depending on the definition of "wetland", they contain between 82 and 158 Pg soil organic carbon (SOC) (Kayranli et al, 2010;Kochy et al, 2015). The surface soil organic carbon (SOC) pool (S-SOCP) and its turnover are sensitive to climate, topography, and hydrological conditions (Wang et al, 2016;Zhang et al, 2017;Pinto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%